HBR's 10 must reads on creative teams collection : 7 books - Grant, Adam, 1981-; Buckingham, Marcus.; Nooyi, Indra, 1955-; Christensen, Clayton M., 1952-2020. (Harvard Business Review Press, 2020)
Ignite the creative spark within your team. For your company to stand out in today's competitive environment, you need to be original. You need to have fresh ideas, exciting products and offerings, and a willingness to experiment. And that starts at the team level. HBR's 10 Must Reads for Creative Teams Collection provides expert advice on how to foster curiosity, encourage better collaboration, and use design thinking to change the way you brainstorm, test, and execute new ideas. Included in this seven-book set are: -HBR's 10 Must Reads on Creativity -HBR's 10 Must Reads on Teams -HBR's 10 Must Reads on Collaboration -HBR's 10 Must Reads on Building a Great Culture -HBR's 10 Must Reads on Design Thinking -HBR's 10 Must Reads on Managing People -HBR's 10 Must Reads on Managing People, Vol. 2 The collection includes seventy articles selected by HBR's editors from renowned thought leaders including Marcus Buckingham, Adam Grant, Francesca Gino, and Indra Nooyi, plus the indispensable article "How Pixar Fosters Collective Creativity" by Ed Catmull. With HBR's 10 Must Reads for Creative Teams Collection, you can break free from the usual and capitalize on originality. HBR's 10 Must Reads paperback series is the definitive collection of books for new and experienced leaders alike. Leaders looking for the inspiration that big ideas provide, both to accelerate their own growth and that of their companies, should look no further. HBR's 10 Must Reads series focuses on the core topics that every ambitious manager needs to know: leadership, strategy, change, managing people, and managing yourself. Harvard Business Review has sorted through hundreds of articles and selected only the most essential reading on each topic. Each title includes timeless advice that will be relevant regardless of an ever-changing business environment